Semantically Related Words May Eliminate Bilingual Language Coactivation in the Deese-Roediger-McDermott Paradigm - Ana Beatriz Arêas da Luz Fontes; Davi Alves Oliveira; Aline Passos; Li-Hao Yeh (Ilha do Desterro, 2023)
This study investigated if bilingual language coactivation would be observed in the context of the Deese-Roediger-McDermott paradigm.  Portuguese-English bilinguals listened to 12 lists of semantically associated words that related to either a cognate or a noncognate critical lure. Participants were instructed to recall as many words as they could and to type them on the computer keyboard. Then, they performed a recognition test with words from the study phase of the recall test, as well as critical lures and unstudied words.  Statistical analyses showed a small but statistically significant difference in the recall of studied words between conditions. No differences were observed in the recognition. We suggest that participants relied more on verbatim than gist trace, which may have reduced language coactivation effects.